Implementasi dan Pengembangan E-Bisnis Terhadap Kemajuan Kurikulum di Era Digital di Islamic Primary School Ibnu Sina Cikarang Selatan - Sikki, Nurhaeni; Mukti, Aryani Kusuma; Abubekar, Udin; Syarifudin; Tjandring, Yuni Cynthia Dewi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The advancement of education in the digital era requires adjustments and breakthroughs in line with technological developments to create an effective and efficient learning environment. One of the most crucial factors in achieving this progress is the implementation of e-business, which integrates technology into the use and renewal of curricula. This study aims to analyze the impact of e-business implementation and development on curriculum advancement at Islamic Primary School Ibnu Sina in Cikarang Selatan. The curriculum at this institution is the result of collaboration between two different organizations, namely Yayasan Ibnu Sina Al-Fatih and Masqod Dirghoem Academy. The primary focus of this research is to explore how e-business, through the use of technology and digital platforms, enhances the quality and relevance of the curriculum while also improving the teaching experience of educators. This study employs a qualitative method with a case study approach at Islamic Primary School Ibnu Sina in Cikarang.